Evaluating the impact of public start-up assistance: results from an econometric approach - Matthias Almus (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper analyzes the medium-term growth performance of firms that exclusively received start-up assistance from programs administered by the Deutsche Ausgleichsbank (DtA), a state owned bank, within two years after startup. I apply a parametric selection approach that controls for two potential sources of self selection (receipt of assistance, complete interview data). The empirical analysis shows that firms receiving assistance perform better in terms of employment growth over a six year period.
Keywords: L21; D92; C35; 330; New Firms; Employment Growth; Evaluation; Selection Bias; Bivariate and Simultaneous Probit; Unternehmensgründung; Öffentliche Kreditvergabe; Wirtschaftsförderung; Wirtschaftspolitische Wirkungsanalyse; Unternehmensentwicklung; Unternehmenswachstum; Beschäftigungseffekt; Schätzung; Deutschland; Deutsche Ausgleichsbank <Bonn>